"One time I fell, but I didn't have to cry." A qualitative study on everyday physical complaints in children - Sterre van der Ziel; Janna M. Gol; Michel J. van Vliet; Judith G. M. Rosmalen (BMC, 2022)
Abstract Objective Young children experience physical complaints, like abdominal pain or minor injuries from playing, almost every day. These experiences may shape how they deal with health issues later in life. While models exist to explain illness perception in adults, information is lacking on the perspective of young children. This qualitative study aimed to explore important themes in the experience of everyday physical complaints in four- and five-year-old children, using children as informants. Study design 30 semi-structured interviews were performed in which four- and five-year-old children were questioned about their experiences with everyday physical complaints. The interviews were double coded using Atlas.ti and subsequently qualitative content analysis was used to define themes. Results All participating children were able to elaborate on their experiences with physical complaints. Three themes emerged from the interviews: causes of complaints, appraisal of complaints, and implications of complaints. In their appraisal of complaints, four- and five-year-old children made a distinction between visible and invisible complaints and real or pretended complaints. Conclusion Four- and five-year-old children can already give details about their experiences with everyday physical complaints. They have developed ideas about the causes and implications of complaints and try to make an appraisal.